Sophisticated Route Calculation Approaches for Microscopic Trafﬁc Simulations - Huebner, Karl; Schuenemann, Bjoern; Radusch, Ilja (EAI Endorsed Transactions on Smart Cities, 2015)
In order to implement meaningful microscopic traffic simulations, a sophisticated calculation of the vehicle routes is essential. In this paper, different route calculation approaches for microscopic traffic simulators are analysed and compared. Various simulations are performed to detect traffic distribution and traffic flow resulting from the used route calculation approaches. To have simulations as realistic as possible, real OD matrices of the city of Fulda (Germany) were used for the evaluation of the different approaches. The results show that simple route calculation algorithms are not appropriate for microscopic traffic simulations. However, approaches that are more sophisticated and that integrate additional heuristics produce good results regarding traffic distribution and traffic flow and can improve iterative techniques to find a user equilibrium.